PENGARUH TERPAAN KAMPANYE DIET PLASTIK DAN BERITA KERUSAKAN LINGKUNGAN TERHADAP PERILAKU PENGGUNAAN PLASTIK - Ayu Wulan Primasari, Dyah; Pudjo Santosa, Hedi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Impacts of plastic use have been acknowledged as an essential and worrying issue for so many countries—including Indonesia. As the second most-producing plastic waste country globally, Indonesia needs various specific handlings to manage its massive waste. Action adjustments for each problem are applied to achieve the goals of collective change. All parties are required to participate. This study aims to reveal the influence of plastic diet campaign exposure and environmental damage news on plastic use behaviour. The theories applied were health behaviour change and media effect. One hundred respondents were taken as the sample. The characteristics are male or female, living in Semarang City, ranging from 19-34 years old—exposed to plastic diet campaigns and environmental damage news. The simple linear regression test results point out that plastic diet campaign exposure on the use of plastic results in a significance value of 0.688. The regression coefficient value is 0.006. This means that the plastic diet campaign exposure variable does not affect plastic use behaviour. Meanwhile, environmental damage news exposure on plastic use behaviour results in a significance value of 0.055. Its correlation coefficient value is 0.092. This means that no effect exists on the plastic use behaviour caused by the variable of environmental damage news exposure.